Argia angelae (Odonata: Zygoptera: Coenagrionidae) sp. nov. from Chapada dos Guimarães, Mato Grosso, Brazil - Vilela, Diogo Silva; Guillermo-Ferreira, Rhainer; Del-Claro, Kleber; Cordero-Rivera, Adolfo (Zootaxa, 2018)
Argia angelae sp. nov. (Holotype ♂, BRAZIL, Mato Grosso, Chapada dos Guimarães, Rio Salgadeira (15°21’25" S, 55°49’51" W, 305 m), 1 xi 2015, D. S. Vilela leg., in LESTES, Cod. ACR 8173A) from Chapada dos Guimarães, Brazil is described, illustrated and diagnosed based on comparison with other known sympatric species of the genus. This species inhabits streams throughout the National Park and a map of its known distribution is provided.